Evaluation of subjective vertical perception among stroke patients: a systematic review - Ferreira, Luana Ribeiro; Ferreira, Flávio José Pereira De Almeida; Campos, Fernanda Aparecida; Luvizutto, Gustavo José; Souza, Luciane Aparecida Pascucci Sande De (Arquivos de Neuro-Psiquiatria, 2021)
Background: Verticality misperception is relatively common among patients after stroke, and it may be evaluated in terms of (a) subjective visual vertical (SVV), (b) subjective haptic vertical (SHV) and (c) subjective postural vertical (SPV). To better understand these assessment methods, we conducted a systematic review of the methodological characteristics of different protocols for evaluating SVV, SHV and SPV among individuals after stroke. Objective: To standardize the methodological characteristics of protocols for evaluating verticality perception after stroke. Methods: We searched the following databases: PUBMED, regional BVS portal (MEDLINE, LILACS, IBECS, CUBMED, Psychology Index and LIS), CINAHL, SCOPUS, Web of Science, Science Direct, Cochrane Library and PEDro. Two review authors independently used the QUADAS method (Quality Assessment of Diagnostic Accuracy Studies) and extracted data. Results: We included 21 studies in the review: most (80.9%) used SVV, eight (38.1%) used SPV and four (19.0%) used SHV. We observed high variability in assessments of verticality perception, due to patient positions, devices used, numbers of repetitions and angle of inclination for starting the tests. Conclusion: This systematic review was one of the first to explore all the methods of assessing verticality perception after stroke, and it provides crucial information on how to perform the tests, in order to guide future researchers/clinicians.
Keywords: Stroke; Health Research Evaluation; Verticality; Subjective Visual Vertical; Subjective Haptic Vertical; Subjective Postural Vertical